Pre‐dam valley reconstruction based on archival spatial data sources: Methods, accuracy, and 3D printing possibilities - Pacina, Jan; Cajthaml, Jiří; Kratochvílová, Darina; Popelka, Jan; Dvořák, Vojtěch; Janata, Tomáš (Transactions in GIS, 2022)
Archival spatial data sources (maps and aerial photographs) allow reconstruction and 3D visualization of landscapes that have been altered by human activity. This article is dedicated to the reconstruction of the 300 km‐long pre‐dam valley of the Vltava River (Czech Republic, Europe) inundated by nine reservoirs built between 1930 and 1992. We used methods based on archival aerial photographs and old maps to reconstruct pre‐dam georelief, which is exceptional because the total area subject to the reconstruction is 1,670 km2. We found that old maps are preferred for terrain reconstruction. The map series “State Map Derived 1:5,000” released between 1950 and 1959 was chosen as the most suitable data source for the pre‐dam valley reconstruction because this map series covers the entire area of interest with elevation information. Based on the processed maps, more than 26,000 km of contour lines were derived by semi‐automatic vectorization. The resulting pre‐dam digital elevation model (DEM) was created using a combination of interpolation techniques. We demonstrated that the methods used for georelief reconstruction under standard conditions should be used carefully while working with such large areas. Geostatistical analysis was performed to verify the accuracy of the resulting DEM. The differences between the model and LiDAR surveyed data were analyzed from three points of view: spatial autocorrelation, normality, and elevation stability. We tested several 3D printing methods for producing a realistic 3D model with a texture applied. The computer numerical control (CNC) milling method was chosen to produce 3D models of the three reservoirs at scales of 1:8,000 and 1:6,000.